2014
DOI: 10.9738/intsurg-d-13-00265.1
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Colony Stimulating Factor (G-CSF)-Producing Esophageal Squamous Cell Carcinoma: A Case Report

Abstract: There are very few reports of esophageal G-CSF-producing cancer. This report describes a case of G-CSF-producing esophageal squamous cell carcinoma we recently encountered. A 70-year-old male patient had Stage III esophageal squamous cell carcinoma. The patient received preoperative chemotherapy, and therapeutic response for the primary lesion was rated as complete response and that of the lymph node metastasis as stable disease. A radical operation was then performed. A relapse to neutrophilia occurred as liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Shimakawa et al also reported a patient with G‐CSF‐producing esophageal cancer who received preoperative chemotherapy (5‐FU, ADM, and CDDP) and whose resected specimens revealed no demonstrable cancer cells. However, liver metastasis developed within 3 months after surgery . In our patient, the early metastasis in the liver may imply that the tumor cells had already metastasized at the time of presentation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Shimakawa et al also reported a patient with G‐CSF‐producing esophageal cancer who received preoperative chemotherapy (5‐FU, ADM, and CDDP) and whose resected specimens revealed no demonstrable cancer cells. However, liver metastasis developed within 3 months after surgery . In our patient, the early metastasis in the liver may imply that the tumor cells had already metastasized at the time of presentation.…”
Section: Discussionmentioning
confidence: 66%
“…To the best of our knowledge, there have been only 10 reported cases of G-CSF-producing esophageal squamous cell carcinomas [13][14][15][16][17][18][19][20][21] (Table 1). The majority of patients were male (nine of ten cases), and the average age of the patients was 63.4 AE 14.2 years (range, 30-81 years).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we diagnosed the patient with G-CSF-producing ESCC. To the best of our knowledge, G-CSF-producing ESCCs are rare, with only 12 cases reported in English literature, including this report [8][9][10][11][12][13][14][15][16][17][18]. In particular, this report is the first case of G-CSF-producing ESCC with choroidal metastasis.…”
Section: Discussionmentioning
confidence: 95%
“…In the present case, neoadjuvant chemotherapy with 5-fluorouracil plus cisplatin was performed because the Japan Clinical Oncology Group (JCOG) 9907 study recommended neoadjuvant chemotherapy followed by surgery as a standard treatment for localized advanced squamous cell carcinomas of the thoracic esophagus [33,34]. In addition, G-CSF-producing tumors have an aggressive clinical course [7,9,10,35]. Chemotherapy with 5-fluorouracil plus cisplatin seemed to be partially effective in the present case, as the leukocytosis was improved, though the serum level of G-CSF was not decreased.…”
Section: Discussionmentioning
confidence: 99%